2022
DOI: 10.17977/um031v9i22022p136
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Family and Peer Support on Learning Habits and Achievements in Online Learning

Abstract: Abstrak: Penelitian ini bertujuan untuk menganalisis peranan dukungan keluarga dan teman sebaya pada masa pembelajaran daring terhadap prestasi belajar mahasiswa melalui kebiasaan belajar. Metode yang digunakan dalam penelitian ini adalah kuantitatif dengan jenis eksplanatori dan teknik analisis data menggunakan partial least square (PLS) dengan konstruk reflektif. Sampel yang diambil adalah mahasiswa pendidikan geografi angkatan tahun 2020 dan 2021 Universitas Siliwangi sebanyak 100 orang mahasiswa secara pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Self-regulated learning has a relationship to student acceleration, especially to the formation of learning motivation and activities to improve students' cognitive (Broadbent & Lodge, 2021). Students' learning motivation is formed by their goals in learning and the ideals they will realize in the future (Azhari et al, 2022;Cheng, 2020).…”
Section: Data Analysis Techniquementioning
confidence: 99%
“…Self-regulated learning has a relationship to student acceleration, especially to the formation of learning motivation and activities to improve students' cognitive (Broadbent & Lodge, 2021). Students' learning motivation is formed by their goals in learning and the ideals they will realize in the future (Azhari et al, 2022;Cheng, 2020).…”
Section: Data Analysis Techniquementioning
confidence: 99%
“…Research has suggested that cultural competency, the ability to connect with and understand a diverse range of populations, can be improved when online delivery systems are designed to bring those from different cultures closer together (Soper & Ukot, 2016). Finally, in terms of peer interactions, research suggests that peer support benefits learners in online forums as it helps them to effectively navigate the course structure and provides a useful secondary tool to succeed in the course (Azhari et al, 2022).…”
Section: Introductionmentioning
confidence: 99%